2021
DOI: 10.3390/s21093207
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Powered Exoskeleton Gait Training on Cardiovascular Function and Gait Performance: A Systematic Review

Abstract: Patients with neurological impairments often experience physical deconditioning, resulting in reduced fitness and health. Powered exoskeleton training may be a successful method to combat physical deconditioning and its comorbidities, providing patients with a valuable and novel experience. This systematic review aimed to conduct a search of relevant literature, to examine the effects of powered exoskeleton training on cardiovascular function and gait performance. Two electronic database searches were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
(351 reference statements)
3
13
0
Order By: Relevance
“…The cardiorespiratory responses assessed using VO 2 in this study were consistent with those reported in previous studies, which indicated that the metabolic demand of walking with an exoskeleton is equivalent to a moderate level of physical activity [ 14 , 15 , 17 , 19 ]. The number of training sessions varied among the studies; however, exercise intensity was similar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The cardiorespiratory responses assessed using VO 2 in this study were consistent with those reported in previous studies, which indicated that the metabolic demand of walking with an exoskeleton is equivalent to a moderate level of physical activity [ 14 , 15 , 17 , 19 ]. The number of training sessions varied among the studies; however, exercise intensity was similar.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, it has been reported that walking with an exoskeleton can elicit activation of trunk muscles below the level of injury, implying that more muscles may be recruited during exoskeleton-assisted walking than activities performed in sitting position [ 13 ]. Previous studies have demonstrated that, according to cardiorespiratory responses, the exercise intensity of walking with a robotic exoskeleton is moderate in patients with SCI despite different training sessions performed before measurements [ 14 , 15 , 16 , 17 , 18 , 19 ]. Although long-term physical activity with a moderate intensity level is known to induce positive cardiorespiratory responses, most studies have not reported changes in cardiorespiratory responses after exoskeleton-assisted walking training with improved proficiency in exoskeleton use.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the currently available studies have reported on the impact of exoskeletons on the QOL and prevention of secondary health complications, on individuals with SCI, are of small scale and are heterogeneous in nature. Moreover, few meta-analyses and reviews have attempted to consolidate the dispersed data to reach more definitive conclusions of the effects of exoskeleton use (14)(15)(16)(17)(18)(19). Many of these reviews included other forms of gait training, such as BWSTT (19), or robotics, such as exoskeletons for upper limbs (16), while others have included the evaluation of exoskeletons beyond individuals with SCI, such as those with a history of stroke (18).…”
Section: Objectives Of This Scoping Reviewmentioning
confidence: 99%
“…Moreover, few meta-analyses and reviews have attempted to consolidate the dispersed data to reach more definitive conclusions of the effects of exoskeleton use (14)(15)(16)(17)(18)(19). Many of these reviews included other forms of gait training, such as BWSTT (19), or robotics, such as exoskeletons for upper limbs (16), while others have included the evaluation of exoskeletons beyond individuals with SCI, such as those with a history of stroke (18). Furthermore, many studies have used the term exoskeleton loosely, often applying the term to different devices, such as reciprocating gait orthosis (RGO), driven gait orthoses, bodyweight-supported treadmill trainers, and some leg braces.…”
Section: Objectives Of This Scoping Reviewmentioning
confidence: 99%
“…Duddy et al [28] examined the effects of powered exoskeleton gait training on cardiovascular function and gait performance via a systematic review. The included studies indicated that powered exoskeleton-assisted training may increase oxygen consumption to a level similar to non-exoskeleton walking, and elevate HR to a greater level than nonexoskeleton waking.…”
Section: Applicationsmentioning
confidence: 99%